Expertise effects on prechoice decision processes and final outcomes - Kuusela, Hannu; Spence, Mark T.; Kanto, Antti J. (European Journal of Marketing, 1998)
Keywords: dept.mkt

How consumers select life insurance policies: A protocol analysis - Kuusela, Hannu; Spence, Mark T (Journal of Professional Services Marketing, 1998)
To gain insight into how people select life insurance policies, we conducted a controlled experiment to see how consumers with varying levels of expertise make choices among life insurance policies when provided relevant information presented in an easy-to-use format. We found that those with greater product class knowledge engage in qualitatively and quantitatively different decision processes than those with less knowledge, and therefore are likely to reach different decisions. Specifically, experts are statistically more likely to engage in pairwise/multiple comparisons and to evoke a greater number of choice criteria. There is directional support that they search for more information as well. For all participants, the number of information searches far exceeded the number of elimination and choice criteria evoked. © 1998 Taylor & Francis Group, LLC.
Keywords: dept.mkt

The effect of expertise on the quality of appraisal services - Spence, Mark T; Thorson, James A (Journal of Real Estate Research, 1998)
Keywords: dept.eco; dept.mkt